2021
DOI: 10.1016/j.bmcl.2020.127667
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of cyclic sulfonamide derivatives as potent inhibitors of SARS-CoV-2

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…However, Compounds 4c exhibited the highest antiviral activity in vitro with IC50 was 758.8108 mM. Our results were in accordance with Shin et al [ 37 ] who proved that cyclic sulfonamide derivatives will be the savior against SARS-CoV-2 because of their IC50 inhibition reached 0.88 μM with no proved cytotoxic effect (CC50 > 25 μM), and high oral bioavailability equaled 77% with good metabolic stability. He et al [ 38 ] tested the antiviral activity of some purine nucleoside derivatives containing a sulfonamide moiety and it was proved that the antiviral activity was related to the immune induction effect.…”
Section: Resultssupporting
confidence: 90%
“…However, Compounds 4c exhibited the highest antiviral activity in vitro with IC50 was 758.8108 mM. Our results were in accordance with Shin et al [ 37 ] who proved that cyclic sulfonamide derivatives will be the savior against SARS-CoV-2 because of their IC50 inhibition reached 0.88 μM with no proved cytotoxic effect (CC50 > 25 μM), and high oral bioavailability equaled 77% with good metabolic stability. He et al [ 38 ] tested the antiviral activity of some purine nucleoside derivatives containing a sulfonamide moiety and it was proved that the antiviral activity was related to the immune induction effect.…”
Section: Resultssupporting
confidence: 90%
“… Gao et al, 2020 ). Of note, it has recently been reported that cyclic sulfonamide derivatives are potent inhibitors (IC 50 = 0.9-3.1 μM) of SARS-CoV-2 in Vero cells (Y. S. Shin et al, 2020 ).…”
Section: Antidiabetic Drugs and Ace2mentioning
confidence: 99%
“…The derivatives 12a and 12d were found to be roughly three-fold more effective as inhibitors of α-glucosidase enzymes compared to acarbose. The increase in bioactivity with the introduction of EWGs in the benzoyl and N-phenyl moieties was also witnessed during the evaluation of previously reported 1,2-benzothiazine-N-arylacetamides as SARS-CoV-2 inhibitors [51]. In the series 12a-m, the variation in the position of nitro, chloro, and bromo substituents failed to enhance the enzymatic inhibition potential of the compounds.…”
Section: α-Glucosidase Inhibition (In Vitro Analysis)mentioning
confidence: 78%
“…The derivative 3 (Figure 1) showed the most promising activity with an IC 50 value of 0.041 µM [49]. Recently, Shin and coworkers reported novel 1,2-benzothiazine-N-arylacetamides as SARS-CoV-2 inhibitors and among them compound 4 (Figure 1) showed robust activity with an IC 50 value of 0.88 µM [51]. Furthermore, 2-(2-(4-bromo-2fluorobenzyl)-1,1-dioxido-2H-benzo[e][1,2]thiazin-4(3H)-ylidene)acetic acid was proved to be a good aldose-reductase inhibitor with an IC 50 value of 0.11 µM [39].…”
Section: Biological Activitymentioning
confidence: 99%